Policy Research Institutes' role in the development of evidence for evidence-based policy making in the United States - Richard V. Burkhauser; Susan V. Burkhauser (Institute of Labor Economics (IZA), 2023)
Policy Research Institutes in the United States play an important role in the creation of evidence for evidence-based policymaking. This is the case with respect to their advocacy for the gathering and broad dissemination of "Big Data" and in the publication of policy analysis in the academic literature using these data. But they play a much more significant role, via non-refereed working papers, in predicting the possible behavioral and distributional consequences of currently proposed policies being considered by the Executive and Legislative branches of government. Historically, however, Policy Research Institutes, both inside- and outside-the-beltway, have also played a less well-understood role. It is the nurturing of those, mostly academic-based economists who, as Members of the Council of Economic Advisers, eventually end up advising Presidents of the United States and their staff on the state of economic knowledge on the economic problems that these policy makers are called to solve via evidence-based policymaking.
Keywords: H0; J0; 330; evidence-based policymaking; Council of Economic Advisers; U.S Policy Research Institutes